Relationship Between Asexual Reproduction of Aurelia coerulea Polyps and Jellyfish Blooms Under the Influence of Temperature Dynamics in Winter and Spring - Zang, Wenxiao; Zhang, Fang; Chi, Xupeng; Sun, Song (Frontiers in Marine Science, 2022)
Aurelia coerulea, as a kind of scyphozoan jellyfish, massively appeared in the coastal waters of China in recent years and caused great damage, but the asexual reproduction of A. coerulea polyp predicted by local temperature could not correspond well to the field abundance of jellyfish in summer. To understand the influence of winter and spring conditions on reproductive process and provides the basis for jellyfish population prediction, A. coerulea polyps, originally reared from ，planula larvae of medusae collected from Jiaozhou Bay (120.2°E, 36.1°N), were investigated at orthometric 3 overwintering temperatures (2, 5, 8℃), 3 spring warming speeds (1℃ increments every 5 days, 7.5 days, 10 days) and 3 feeding frequencies (once per 9 days, 6 days, 3 days), which representing the range of environment conditions in winter and spring where they existing. Polyps had earlier strobilation, higher strobilation frequency, more ephyra and bud production during warmer winter, but had intensive strobilation after colder winter when the temperature began to rise in spring. When warming speed was fast in spring, the percentage of the first strobilation was higher and ephyra released more intensively. However, when warming speed was slow in spring, the polyp could conduct secondary strobilation, resulting in higher strobilation frequency and more ephyrae with a longer period. High feeding frequency helped polyp accumulate more energy and promote asexual reproduction, especially beneficial to the second strobilation. This experiment shows that winter and spring temperature has a significant effect on the asexual reproduction of polyp, but this does not necessarily lead to jellyfish outbreaks. In the context of global warming, whether reproduction of polyps will eventually lead to the outbreak of jellyfish needs to be multifacetedly analyzed based on the complex situation in the field, such as the concentration and timing of jellyfish appearance, and their interactions with other species.